Association Between Maternal Perceived Stress in All Trimesters of Pregnancy and Infant Atopic Dermatitis: A Prospective Birth Cohort Study - Shen, Qianwen; Zhang, Qianqian; Zhao, Jiuru; Huang, Zhen; Wang, Xiaoli; Ni, Meng; Tang, Zheng; Liu, Zhiwei (Frontiers in Pediatrics, 2020)
Background: Currently, most studies indicate that there is a potential link between maternal psychologic stress and the risk of atopic dermatitis (AD) in offspring. However, it is unknown which trimester of pregnancy is most sensitive to maternal stress in terms of risk of infant AD and whether the changes of maternal stress level in different trimesters of pregnancy may be associated with infant AD. In this study, we aimed to investigate the association between maternal perceived stress across three trimesters of pregnancy and AD in infants at 6 months. Methods: A total of 1,638 pregnant women participated in the population-based birth cohort study. Maternal prenatal stress was assessed by self-report questionnaires during each trimester. Infant AD was diagnosed at age 6 months, according to the UK Working Party diagnostic criteria. Univariate and multivariate logistic regression models were used to analyze the association between maternal prenatal stress in each trimester of pregnancy and infant AD. Results: Maternal perceived stress in the 2nd trimester was associated with AD in infants at 6 months (aOR 1.56; 95% CI 1.08–2.25, P = 0.019). Furthermore, increased level of perceived stress from the 1st to the 2nd trimester (aOR 2.05, 95% CI 1.33–3.15, P = 0.001) and from the 1st to the 3rd trimester (aOR 1.92, 95% CI 1.22–3.00, P = 0.004) were also associated with the risk of infant AD at 6 months. Conclusion: A high level of maternal perceived stress in the 2nd trimester and increased level of perceived stress from the 1st to the 2nd and 3rd trimesters of pregnancy may increase the risk of offspring developing AD at 6 months.